Efek Moderasi Kompetensi Sumber Daya Manusia Pada Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan Badan Amil Zakat Nasional (Baznas) di Indonesia - ZIEKWAN; Diah PA, Enggar; Wiralestari, Wiralestari (Magister Ilmu Akuntansi Universitas Jambi, 2024)
The purpose of this research was to determine Moderating Effect of Human Resources Competency on Factors that Influencing The Financial Statements Quality Of Badan Amil Zakat Nasional (Baznas) In Indonesia. The sample in this study was 86 (eighty-six) Regional BAZNAS throughout Indonesia. The data used in the study were primary data. The analysis method used was Moderated Regression Analysis (MRA) using the SPSS 26 program. The results showed that the Implementation of Accounting Standards and Accounting Information Systems had a significant positive effect on the Quality of Financial Reports, while the Internal Control System, Financial Supervision, Organizational Commitment, and Implementation of Good Governance did not affect the Quality of Financial Reports. Human Resource Competence was able to moderate the effect of the Implementation of Accounting Standards and Accounting Information Systems on the Quality of Financial Reports, while the Internal Control System, Financial Supervision, Organizational Commitment, and implementation of good governance were not able to be moderated by Human Resource Competence.